2017
DOI: 10.5539/res.v9n3p176
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Business Intelligence on the Effectiveness of the Organization (Case Study: Airline Companies in Iran)

Abstract: Given the increasing competition between airlines companies in the country and equipping them with modern information technologies, establishment of knowledge management system in airline industry can increase the effectiveness of business intelligence system and lead to effectiveness of this industry. The aim of this study was to identify the effects of strategy, structure, processes and organizational culture on the effectiveness of organization and mediating role of business intelligence systems in Iran's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Arefin et al (2015) established that BI system is more effective in impacting firm's performance in a situation where there is decentralized structure and speedy relay of information to top management. The connection between organisation strategy and BI effectiveness is also apparent in previous studies (Rayat & Kelidbari, 2017). Empirical research by Isik et al (2013 confirmed that decision environment does impact the relationship between BI success and capabilities.…”
Section: Discussion Of Findingsmentioning
confidence: 56%
See 2 more Smart Citations
“…Arefin et al (2015) established that BI system is more effective in impacting firm's performance in a situation where there is decentralized structure and speedy relay of information to top management. The connection between organisation strategy and BI effectiveness is also apparent in previous studies (Rayat & Kelidbari, 2017). Empirical research by Isik et al (2013 confirmed that decision environment does impact the relationship between BI success and capabilities.…”
Section: Discussion Of Findingsmentioning
confidence: 56%
“…The findings are in agreement with recent empirical results. For example, results from research conducted by Rayat and Kelidbari (2017) confirmed culture has a significant impact on the effectiveness of BI. Fink et al (2017) reported that business value of BI depends on the complementarity and compatibility with institutional routines through which learning generates new knowledge.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Structural Equation Modelling demonstrated that the causal relationship between strategic intelligence and employee performance was satisfactory. Mahsa and Hamid (2017) examined the effects of business intelligence on the effectiveness of the Organization using case study of Airline Companies in Iran. In view of the growing competition among airlines companies in Iran and the need to equip them with the latest information technologies, the implementation of knowledge management systems in the airline industry can improve the efficiency of the business intelligence system in the industry and lead to the efficiency of the industry.…”
Section: Emperical Reviewmentioning
confidence: 99%